2012
DOI: 10.1002/ibd.22930
|View full text |Cite
|
Sign up to set email alerts
|

Detection and differentiation of inflammatory versus fibromatous Crohnʼs disease strictures: Prospective comparison of 18F-FDG-PET/CT, MR-enteroclysis, and transabdominal ultrasound versus endoscopic/histologic evaluation

Abstract: Detection rates of the strictures were not significantly different between (18) FDG-PET/CT, MR-enteroclysis, and ultrasound. Despite good stricture detection rates relating to our gold standard, (18) FDG-PET/CT nor MR-enteroclysis nor ultrasound can accurately differentiate inflamed from fibrotic strictures. A combination of MR-enteroclysis and ultrasound as well as a combination of (18) FDG-PET/CT and ultrasound resulted in a 100% detection rate of strictures requiring surgery or endoscopic dilation therapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 23 publications
0
58
0
Order By: Relevance
“…In patients with CD, mucosal disease activity is routinely assessed by endoscopy and histologic evaluation, but in recent studies it has been evaluated the translational potential of noninvasive 18F-FDG PET/CT for the assessment of mucosal damage in CD, as we have done in our second case report (6). The usefulness of this method becomes relevant as an alternative to MRI enterography in the group of patients in which it is not possible to perform an adequate bowel preparation, as in our second case.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CD, mucosal disease activity is routinely assessed by endoscopy and histologic evaluation, but in recent studies it has been evaluated the translational potential of noninvasive 18F-FDG PET/CT for the assessment of mucosal damage in CD, as we have done in our second case report (6). The usefulness of this method becomes relevant as an alternative to MRI enterography in the group of patients in which it is not possible to perform an adequate bowel preparation, as in our second case.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PET/MRI exposes patients to less radiation than PET/CT. A study conducted by Lenze et al already demonstrated that the combination of individual examinations yielded better results than 18-F-FDG PET/CT, MR enteroclysis and transabdominal ultrasound alone in the detection and differentiation of acute inflammatory changes over fibrotic strictures in Crohn's disease patients alone [53]. It is expedient for PET and MR data to be acquired simultaneously when PET/MRI is employed.…”
Section: Hybrid Imaging: Pet/mrmentioning
confidence: 99%
“…Detection rates ofthe strictures were not significantly different between FDG-PET/CT, MR enteroclysis, and US; nevertheless, these techniques did not accurately differentiate inflamed from fibrotic strictures. Only a combination of these techniques resulted in a 100% detection rate of strictures requmng surgery or endoscopic dilation therapy, suggesting the combination of these methods as an alternative to endoscopy at least in the group of patients not able to perform an adequate bowel preparation (24).…”
Section: Fdg-pet and Petict In The Assessment Ofibd In Adult Patientsmentioning
confidence: 99%